Análise de sobrevida de pacientes com câncer de mama atendidas no Hospital Santa Rita de Cássia, na cidade de Vitória, Espírito Santo - Albrecht, Cristina Arthmar Mentz (2011)
Breast cancer is a disease with high and growing incidence, and its treatment has psychological and physical consequences on the affected women s cure and rehabilitation. With regard to this subject, the average survival period analysis allows the identification of the disease stage, the availability of health services to the population and the adopted treatment effectiveness. Objectives: To describe the mean profile of women diagnosed with breast cancer who received treatment at the Santa Rita Hospital in Vitoria, Espírito Santo State, Brazil, during the interval from January 2000 to December 2005; to estimate the average survival period in breast cancer patients and to examine its relation to socioeconomic, demographic and clinical variables. Methodology: Three studies were performed: one of profile classified as descriptive observational of transverse nature; another of mortality described as descriptive observational of longitudinal nature; and the survive one about women with breast cancer diagnosed and treated at the Santa Rita Hospital from January 1st 2000, to December 31 2005. To estimate the survival period in general and by stratum, the Kaplan Meyer method was employed. The independent effect of variables was checked by Cox s model of multivariate proportional risk, while statistical significance was tested through the log-rank method. The analysis used the Statistical Package of Social Science software on its 18.0 version. Results: The Hazard ratio analysis has shown major risk associated with: (i) low schooling level; (ii) patients origin from the Sistema Único de Saúde (the Brazilian state run Health Care System); (iii) estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 (Her2) overexpression (iv) negative tumoral indicator p53 protein (v) advanced staging (vi) metastasis presence, and (vii) relapse. In the multivariate analysis, only staging and metastasis have shown association with the survival period. Conclusion: The link between mortality and staging reinforces the necessity of breast cancer early diagnose. Accordingly, it was observed that the awareness of the female population with regard to both the early detection precautions and the assurance of access to the health services is essential to the disease early diagnose and to promote a more extensive survival period.